2012
DOI: 10.1039/c2dt11938b
|View full text |Cite
|
Sign up to set email alerts
|

Copper(i) and nickel(ii) complexes with 1 : 1 vs. 1 : 2 coordination of ferrocenyl hydrazone ligands: Do the geometry and composition of complexes affect DNA binding/cleavage, protein binding, antioxidant and cytotoxic activities?

Abstract: A new series of geometrically different complexes containing ferrocenyl hydrazone ligands were synthesised by reacting suitable precursor complex [MCl 2 (PPh 3 ) 2 ] with the ligands HL 1 or HL 2 (where M = Cu(II) or Ni(II); HL(5) and [Ni(L 2 ) 2 ] (6) were characterised by various spectral studies. Among them, complexes 3 and 5 characterised by single crystal X-ray diffraction showed a distorted tetrahedral structure for the former with 1 : 1 metal-ligand stoichiometry, but a distorted square planar geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(48 citation statements)
references
References 67 publications
0
47
0
1
Order By: Relevance
“…All the complexes did not cause any damage to the healthy cells (NIH 3T3) indicating that they are non-toxic to normal cells as expected for a better drug. On comparison with that of the other reported nickel hydrazone complexes 63 our complexes showed better activity and the same was included in Table 6. However, the hydrazone ligands 1-3 and the nickel precursor complex did not show any activity under the same experimental conditions.…”
Section: Antioxidant Activitiesmentioning
confidence: 87%
“…All the complexes did not cause any damage to the healthy cells (NIH 3T3) indicating that they are non-toxic to normal cells as expected for a better drug. On comparison with that of the other reported nickel hydrazone complexes 63 our complexes showed better activity and the same was included in Table 6. However, the hydrazone ligands 1-3 and the nickel precursor complex did not show any activity under the same experimental conditions.…”
Section: Antioxidant Activitiesmentioning
confidence: 87%
“…In order to differentiate these above types of quenching, representative UV/Vis absorption spectroscopy of BSA in the absence and presence of complex 1 is shown in Figure 10 (for complexes 2 , 3 and 4 , see Figure S7, Supporting Information). The weak absorption peak at 279 nm showed an increase in intensity in the absence of metal complex, which revealed that the fluorescence quenching mainly due to static quenching procedure by forming a complex‐BSA ground state 30,31…”
Section: Resultsmentioning
confidence: 98%
“…Synchronous fluorescence spectra provide information on the molecular microenvironment, particularly in the vicinity of the fluorophore functional groups. For BSA, the synchronous fluorescence Δ λ value of 15 nm is the characteristic of the tyrosine residues, and the Δ λ value of 60 nm is the characteristic of the tryptophan residues 30,31. In order to research the structural changes of BSA in presence of complexes, synchronous fluorescence spectra with addition of complexes were recorded at both Δ λ = 15 nm and 60 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Because the change in hypochromism and strong bathochromic shift usually are related to the intercalative binding, which can be explicated as the function of the aromatic chromophore and DNA base pairs [15]. In order to quantitatively measure the binding strength of complexes with DNA, the binding constants K b can be obtained by using the following formula [16]:…”
Section: Uv-vis Spectramentioning
confidence: 99%